Meloidogyne inornata em feijoeiro: aspectos biológicos e reação de cultivares - Dadazio, Tais Santo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The culture of the bean has its limited productivity by biotic factors, such as plant parasitic nematodes. Several species have been reported causing damage to the culture, especially those belonging to the genus Meloidogyne. Recently, a new species was reported parasite culture in State of Paraná, M. inornata. Due to this report, the present study aimed to generate information about its life cycle and feeding sites under different temperatures, compared to M. incognita, characterize the resistance reaction of 32 bean cultivars M. inornata and check the potential damage of this nematode. The reaction test was conducted in a greenhouse, and inoculated 2,000 eggs / plant. After 50 days, it was found that all cultivars susceptible behaved as against nematodes, with RF ranging from 13.69 to 94.71 for the color group and 17.31 to 80.46 for the group black. The damage level experiment was also carried out in a greenhouse, the inoculation of the following population densities of M. inornata in bean cv. Tuiuiú: 0 (control); 0.0625; 0.125; 0.25; 0.5; 1; 2; 4; 16; 32; and 64 eggs per cm3 of soil. The tolerance limit set for cultivating Tuiuiú inoculated with M. inornata was 9.9 cm3 of soil nematodes, that is, from that population density the plant becomes damaged by nematodes. Regarding the comparative biology of M. inornata with M. incognita, the experiments were conducted in a growth chamber type BOD at temperatures of 18 ° C, 25 ° C and 32 ° C. The results showed that at a temperature of 25 ° C is optimal for the development of both species, while at 18 ° C, the cycle of both species is retarded and 32 ° C, the cycle is accelerated; Furthermore, both species formed a similar permanent feeding site.

A cultura do feijoeiro tem sua produtividade limitada por fatores bióticos, como os fitonematoides. Diversas espécies de têm sido relatadas causando danos à cultura, especialmente aquelas pertencentes ao gênero Meloidogyne. Recentemente, uma nova espécie foi relatada parasitando a cultura no Estado do Paraná, M. inornata. Em função desse relato, o presente trabalho teve como objetivo gerar informações acerca de seu ciclo biológico e sítio de alimentação, sob diferentes temperaturas, comparadas a M. incognita, caracterizar a reação de resistência de 32 cultivares de feijoeiro a M. inornata e verificar o potencial de danos desse nematoide. O teste de reação foi realizado em casa de vegetação, sendo inoculados 2.000 ovos/ planta. Após 50 dias, concluiu-se que todas as cultivares comportaram-se como suscetíveis frente ao nematoide, com FR variando de 13,69 a 94,71, para o grupo cores, e de 17,31 a 80,46, para o grupo preto. O experimento de nível de danos também foi realizado em casa de vegetação, inoculando-se as seguintes densidades populacionais de M. inornata em feijão cv. Tuiuiú: 0 (testemunha); 0,0625; 0,125; 0,25; 0,5; 1; 2; 4; 16; 32; e 64 ovos por cm3 de solo. O limite de tolerância estabelecido para a cultivar Tuiuiú inoculada com M. inornata foi de 9,9 nematoides cm3 de solo, ou seja, a partir dessa densidade populacional a planta passa a ser danificada pelo nematoide. Em relação à biologia comparativa de M. inornata com M. incognita, os experimentos foram realizados em câmara de crescimento do tipo BOD, nas temperaturas, de 18°C, 25°C e 32°C. Os resultados mostraram que temperatura de 25°C é a ideal para o desenvolvimento de ambas as espécies, enquanto aos 18°C, o ciclo de ambas as espécies é retardado e aos 32°C, o ciclo é acelerado; além disso, ambas as espécies formaram um sítio de alimentação permanente semelhante
Meloidogyne inornata in bean: biological aspects and reaction cultivars
Keywords: Nematoide de cisto da soja; Feijão - Doenças e pragas; Feijão - Cultivo; Soybean cyst nematode